Changes in circulating microRNA and arterial stiffness following high‐intensity interval and moderate intensity continuous exercise. Issue 9 (1st May 2020) - Sapp, Ryan M.; Chesney, Catalina A.; Eagan, Lauren E.; Evans, William S.; Zietowski, Evelyn M.; Prior, Steven J.; Hagberg, James M.; Ranadive, Sushant M.
Abstract: High‐intensity interval (HII) exercise elicits distinct vascular responses compared to a matched dose of moderate intensity continuous (MOD) exercise. However, the acute effects of HII compared to MOD exercise on arterial stiffness are incompletely understood. Circulating microRNAs (ci‐miRs) may contribute to the vascular effects of exercise. We sought to determine exercise intensity‐dependent changes in ci‐miR potentially underlying changes in arterial stiffness. Ten young, healthy men underwent well‐matched, 30‐min HII and MOD exercise bouts. RT‐qPCR was used to determine the levels of seven vascular‐related ci‐miRs in serum obtained immediately before and after exercise. Arterial stiffness measures including carotid to femoral pulse wave velocity (cf‐PWV), carotid arterial compliance and β‐stiffness, and augmentation index (AIx and AIx75) were taken before, 10min after and 60min after exercise. Ci‐miR‐21‐5p, 126‐3p, 126‐5p, 150‐5p, 155‐5p, and 181b‐5p increased after HII exercise ( p < .05), while ci‐miR‐150‐5p and 221‐3p increased after MOD exercise ( p = .03 and 0.056). One hour after HII exercise, cf‐PWV trended toward being lower compared to baseline ( p = .056) and was significantly lower compared to 60min after MOD exercise ( p = .04). Carotid arterial compliance was increased 60min after HII exercise ( p = .049) and was greater than 60min after MOD exercise ( p = .02). AIx75 increased 10 min after both HII and MOD exercise ( p < .05). There were significant correlations between some of the exercise‐induced changes in individual ci‐miRs and changes in cf‐PWV and AIx/AIx75. These results support the hypotheses that arterial stiffness and ci‐miRs are altered in an exercise intensity‐dependent manner, and ci‐miRs may contribute to changes in arterial stiffness. Abstract : We identified a reduction in central artery stiffness and an increase in carotid arterial compliance one hour after acute high intensity interval (HII) cycling exercise, that was not seen after moderate intensity continuous cycling (MOD). HII and MOD elicited distinct increases in the concentrations of circulating microRNAs (ci‐miRs) with potential regulatory roles in arterial stiffness. Significant correlations between some of the changes in ci‐miRs and measures of arterial stiffness suggest potential mechanistic roles for ci‐miRs.